Duration of plasma oxytetracycline levels in neonatal pigs - Schoneweis, D.; Hummels, S.; Schulteis, L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Samples from neonatal pigs were evaluated to determine the persistence of plasma oxytetracycline after injecting LA 200®. Significant (minimum of .2 mcg/ml) amounts of oxytetracycline were found in all samples 96 hours after the injection, and oxytetracycline still persisted in many pigs after 168 hours.
Keywords: Swine; Plasma oxytetracycline; Neonatal pigs